A Study of Listeners of the Song Haro Hara Songs from the Nyawöung Album (2000) - Wirandi, Rika; Putra, Rizki Mona Dwi; Wijaya, Reza Sastra (Gondang: Jurnal Seni dan Budaya, 2025)
The research of Listeners' Study of Haro Hara Songs on Nyawöung 2000 Album aims to observe how listeners' experiences and interpretations of protest songs that emerged and developed during the armed conflict in Aceh in 2000-2003. The protest music that is the topic of this research refers to the category of songs created by local Acehnese musicians in the genre of regional pop and pop-authentic music with themes and lyrics inspired by several series of bloody events that have occurred in Aceh during the conflict, especially after the lifting of the status of the Military Operation Area (DOM) in 1998. Listener studies are the focus of this research as an effort to construct the memory, experience, and interpretation of listeners of these protest songs during the conflict and post-conflict period in Aceh. The method used in this research is a qualitative method using a phenomenological approach by emphasizing on extracting data related to the experiences and interpretations of listeners of protest songs by using data collection techniques using questionnaires to several listeners who became participants with three categories, namely: participants or listeners in the age group of generation X (born 1965-1980); age group of generation Y / Millennial (born 1981-1994); and participants or listeners in the age group of generation Z (born 1995-2010). This research uses framing analysis technique which consists of three frames of analysis to classify the interpretation of song listeners, namely, Diagnostic Framing, Prognostic Framing, Motivational Framing. The results of this study show that, participants who are listeners from the age group of generation X, generation Y, and generation Z stated that the song Haro Hara is a song that describes the state of Aceh during the GAM and RI conflict. The lyrics of the song are considered very straightforward with the interpretation classification of all respondents showing an average as diagnostic framing.